Pengaruh Kepercayaan, Kemudahan, Kualitas Informasi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Aplikasi Lazada (Studi Kasus Pengguna Aplikasi Lazada di Kota Sampang Madura) - Firmansyah, Oktova Rian; Arifin, Rois; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The Purpose Of This Research Is To Analyze The Impact Of Trust, Convenience, Information Quality, And Service Quality On Purchasing Decisions On The Lazada Application. The Research Was Conducted In The City Of Sampang, Madura, Using A Purposive Sampling Technique For Sampling. Data Was Collected By Distributing Questionnaires Using Google Form To The Local Community. The Sample Size Was Determined Based On The Ferdinand Formula, Which Resulted In 84 Respondents. The Analytical Methods Used In This Research Include Instrument Tests (Validity And Reliability), Normality Tests, Classical Assumption Tests (Multicollinearity And Heteroscedasticity), Multiple Linear Regression Analysis, Hypothesis Testing (F Test And T Test), And The Coefficient Of Determination Test (Adjusted R2 ). Data Were Analyzed Using IBM SPSS Version 23. The Results Showed That Trust, Convenience, Information Quality And Service Quality Simultaneously Influenced Purchasing Decisions. Partially, Trust, Convenience And Quality Of Information Influence Purchasing Decisions, Although Not Significantly. Meanwhile, Service Quality Is Proven To Have A Significant Influence On Purchasing Decisions.  Keywords: Trust, Convenience, Information Quality, Service Quality, Purchasing Decisions.